Pengaruh Profesionalisme Dan Kepribadian Terhadap Kinerja Guru - Bahrudi Efendi Damanik; Susiani Susiani; Fitri Rizki; Ika Okta Kirana (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This research was conducted aiming to determine the effect of professionalism, personality on teacher performance partially and simultaneously. The method used is a survey method with a quantitative approach, namely an approach that uses numbers that are processed through non-parametric statistical analysis in analyzing correlational research results. This research is included in the associative type, which contains a complete picture of the relationship between one variable and another variable, has a linear relationship type, because basically it wants to see the relationship between the independent variables, namely teacher professionalism and personality, with a sample size of 51 people. The conclusion of the research simultaneously that professionalism and personality variables have a positive and significant effect on teacher performance can be seen where the F-count value > F-table (27.672 > 2.790), partially the professionalism variable has a positive and significant effect on teacher performance where the t-count value > t-table (3.295 > 2.000), and partially the personality variable has a positive and significant effect on teacher performance where the value of tcount > ttable (3.884 > 2.000).